Study of asymmetrically heated flows passing through gas-pressurized solar receivers using Direct Numerical Simulations. (February 2023) - David, Martin; Toutant, Adrien; Bataille, Françoise
Highlights: DNS of highly anisothermal and turbulent channel flows are performed and analyzed. Integral values, turbulence statistics, PDF, and spectra are investigated. Differences and similarities between wall heat flux and wall friction are highlighted. PDF of wall heat flux and wall friction are well fitted with skewed Gaussian models. Ratio between wall heat flux and wall friction is linked to turbulent structure size. Abstract: Solar receiver flows are very complex since the heating fluid is strongly turbulent and asymmetrically heated at high temperature levels. To deepen the understanding of these flows, four DNS have been performed in different fluid heating configurations. The Navier-Stokes and the energy equations are solved under the low Mach approximation and the coupling between the dynamics and the temperature is taken into account. A simplified geometry of solar receiver is used and consists in a bi-periodical channel flow with fixed wall temperatures. The hot and cold wall temperatures are respectively 1300K and 900K and the mean friction Reynolds number is 820. Integral, mean and fluctuating quantities are investigated. Afterwards, quantitative and qualitative studies of instantaneous fields of wall heat flux and wall friction are carried out. In particular, probability density functions and 1D spectral analyses are discussed. This work highlights the strong coupling between the dynamics and the temperature. Focusing on wall heat fluxes, it seems that the ratio between the fluctuations and the mean quantity is weakly dependent of the studied conditions and is about 0.44 at both walls in all the simulations. The wall heat flux and the wall friction are highly correlated. The probability density functions indicate that the most probable wall heat fluxes, respectively wall frictions, are below the mean wall heat flux, respectively wall friction. They can be well approximated with skewed Gaussian distributions. The turbulent structures associated with wavenumbers lying between k x + = 0.03 and k x + = 0.05 and those associated to small wavenumbers in the spanwise direction seems to favor the heat transfer while keeping a wall friction relatively low.